Concomitant inhibition of oxidative stress and angiogenesis by chronic hydrogen‐rich saline and N‐acetylcysteine treatments improves systemic, splanchnic and hepatic hemodynamics of cirrhotic rats. Issue 5 (6th August 2014) - Lee, Pei‐Chang; Yang, Ying‐Ying; Huang, Chien‐Sheng; Hsieh, Shie‐Liang; Lee, Kuei‐Chuan; Hsieh, Yun‐Cheng; Lee, Tzung‐Yan; Lin, Han‐Chieh
Abstract : Aim: In cirrhosis, increased oxidative stress leads to systemic and splanchnic hyperdynamic circulation, splanchnic angiogenesis, portosystemic collateral formation, hepatic endothelial dysfunction, increased intrahepatic resistance and the subsequent portal hypertension. Like N‐acetylcysteine, hydrogen‐rich saline is a new documented antioxidant with the potential to treat the complications of liver diseases. Methods: In this study, hemodynamics, splanchnic angiogenesis and hepatic endothelial dysfunction were measured in common bile duct ligation (BDL)‐cirrhotic rats receiving 1‐month treatment of vehicle, N‐acetylcysteine and hydrogen‐rich saline immediately after BDL. Additionally, acute effects of N‐acetylcysteine and hydrogen‐rich saline on vascular endothelial growth factor (VEGF)‐induced tubule formation and migration of human umbilical vein endothelial cells (HUVEC) were also evaluated. Results: The data indicate that 1‐month treatment of N‐acetylcysteine or hydrogen‐rich saline significantly ameliorated systemic and splanchnic hyperdynamic circulation, corrected hepatic endothelial dysfunction, and decreased intrahepatic resistance and mesenteric angiogenesis by inhibiting inflammatory cytokines, nitric oxide, VEGF and reducing mesenteric oxidative stress in cirrhotic rats. In vivo studies revealed that acute co‐incubation of N‐acetylcysteine or hydrogen‐rich saline with VEGF effectively suppressed VEGF‐induced angiogenesis and migration of HUVEC accompanied by decreasing of oxidative stress and inflammatory cytokines. Conclusion: Both hydrogen‐rich saline and N‐acetylcysteine alleviate portal hypertension, the severity of portosystemic collaterals, mesenteric angiogenesis, hepatic endothelial dysfunction and intrahepatic resistance in cirrhotic rats. N‐Acetylcysteine and the new antioxidant, hydrogen‐rich saline are potential treatments for the complications of cirrhosis.